Inferior alveolar nerve transposition with involvement of the mental foramen for implant placement - De Vasconcelos, Juliano Alencar; Ávila, Gisseli Bertozzi; Ribeiro, José Carlos; Dias, Sérgio Cândido; Pereira, Luciano José (My University, 2008)
Inferior Alveolar Nerve (IAN) transposition is an option for prosthetic rehabilitation in cases of moderate or even severe bone reabsorption for patients that do not tolerate removable dentures. The aim of the present report is to describe an inferior alveolar nerve transposition with involvement of the mental foramen for implant placement. The surgical procedure was performed under local anesthesia, by the inferior alveolar, lingual and buccal nerve blocking technique. Centripetal osteotomy was performed, and bone tissue was removed, leaving the nerve tissue free in the foramen area. After that, transsection of the incisor nerve was performed, and lateral osteotomy was started from the buccal direction, toward the trajectory of the IAN. The procedure was concluded, by making use of a delicate resin spatula to manipulate the vascular-nervous bundle. The drilling sequence for placing the dental implants was performed, and autogenous bone was harvested using a bone collector attached to the surgical suction appliance. After the implants were placed, the bone tissue previously collected during the osteotomies and drilling processes was placed in order to protect the IAN from contact with the implants. The surgical protocol for inferior alveolar nerve transposition, followed by implant placement presented excellent results, with complete recovery of the sensitivity, seven months after the surgical procedure. © Medicina Oral S. L. C.I.F.
Keywords: Alveolar nerve transposition; Dental implants